1999
DOI: 10.1088/0957-4484/10/1/008
|View full text |Cite
|
Sign up to set email alerts
|

Nanometre-scale oxidation of silicon surfaces by dynamic force microscopy: reproducibility, kinetics and nanofabrication

Abstract: Local oxidation of silicon surfaces by scanning probe microscopy is a very promising lithographic approach at nanometre scale. Here, we present two approaches to optimize the oxidation for nanofabrication purposes: (i) we analyse the reproducibility and kinetics of the oxidation of Si(100) surfaces when there is no tip and sample mechanical contact and (ii) we study the effect of modulating the voltage in the aspect ratio of the oxide structures grown. The finite tip-sample separation has remarkable practical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…In previous contributions 16,20 we have demonstrated that the oxidation kinetics of silicon surfaces in noncontact follows the same behavior than in contact SPM. As a consequence the results obtained by Dagata et al 15 about the oxidation mechanism should also apply here.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous contributions 16,20 we have demonstrated that the oxidation kinetics of silicon surfaces in noncontact follows the same behavior than in contact SPM. As a consequence the results obtained by Dagata et al 15 about the oxidation mechanism should also apply here.…”
Section: Introductionmentioning
confidence: 87%
“…[7][8][9][10][11][12][13][14] Recently this field has experienced a renovated interest. For one side, several results have contributed to an increased understanding of the oxidation mechanism in silicon surfaces 15,16 and its kinetics. [17][18][19][20] Simultaneously, the reproducibility, aspect ratio and control of the oxide size have been improved by performing the oxidation with an oscillating tip while keeping the tip and the sample several nanometers apart 20 and by modulating the tip-sample voltage.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a negative bias of 10 V can result in a conversion rate of about 30 000 nm/s for a 5-nm-thick Si 3 N 4 film in ambience. In the case of Si anodic AFM oxidation, 11 it is widely accepted that the mechanism for the process is essentially controlled by the adsorption of water from the environment on the surface. The negatively charged oxygen ions are injected from the water and transported by the high electric field through the oxide layer to the Si/SiO 2 interface, where they react with the positively charged holes and Si to form SiO 2 .…”
Section: Spem System At Srrcmentioning
confidence: 99%
“…Based on this idea, anodization with a pulsed mode composed of successive forward and reverse bias pulse trains was shown to be effective in enhancing the anodization rate in the direction perpendicular to Si surfaces. 20,28 This pulsed mode operation was investigated as a possible solution for the anodization of carbonaceous films. 29 Since the reproducibility of the anodization was more sensitive for the dot-like patterns prepared without scanning compared with the line patterns discussed above, anodization of dot-like patterns will be mainly treated in the following.…”
Section: Pulsed Bias Anodization Versus Constant Bias Anodizationmentioning
confidence: 99%
“…13,20͒ This approach opened the way for higher reliability during the patterning process and also gave additional information about the role played by the water meniscus. 20 The SP lithography demonstrated patterning of not only some simple features but also more complex ones leading to prototypes of unique devices. Among these devices we can find a 0.1-m-gate metal-oxide-semiconductor field-effect transistor, 21 a side-gated transistor on a silicon-on-insulator wafer, 22 and a single electron transistor.…”
Section: Introductionmentioning
confidence: 99%